Produksi Video Company Profil Fakultas Teknologi Universitas Battuta Medan dengan Adobe Premier CC 2019 - Surya Darma; John John; M. Rhifky Wayahdi; Ihsan Primas Danu (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This study aims to produce a company profile video for the Faculty of Technology, Battuta University, Medan using Adobe Premiere CC 2019 software. This company profile video is designed to provide a clear picture of the vision, mission, organizational structure, facilities, and superior programs at the Faculty of Technology, Battuta University, Medan. The production process of this video goes through several stages, namely planning, shooting, processing visual materials, and editing to produce a video that is in accordance with the communication objectives to be conveyed. Adobe Premiere CC 2019 was chosen as the main tool in video editing because of the ability of this software to provide various professional editing features, such as transition settings, visual effects, color adjustments, and audio processing that supports the quality of the final video results. The results of this study are in the form of a company profile video that can be used as a promotional media, which is expected to improve the image and attractiveness of the Faculty of Technology, Battuta University, Medan in the eyes of prospective students and the general public. With this video, it is hoped that information about the faculty can be conveyed more effectively and attractively.